Cytological and microbiological characteristics of middle ear effusions in brachycephalic dogs. (14th May 2020) - Milne, Elspeth; Nuttall, Tim; Marioni‐Henry, Katia; Piccinelli, Chiara; Schwarz, Tobias; Azar, Ali; Harris, Jennifer; Duncan, Juliet; Cheeseman, Michael
Abstract: Background: Middle ear effusion is common in brachycephalic dogs with similarities to otitis media with effusion in children. Association with the cranial and eustachian tube morphology and bacterial infection is suspected in both species. Hypothesis/objectives: To determine cytological and bacteriological features of middle ear effusions in dogs, provide information on histological features, and further assess the dog as a model of the human disease. Animals: Sixteen live dogs, 3 postmortem cases of middle ear effusion, and 2 postmortem controls. Methods: Prospective; clinical investigation using computed tomography, magnetic resonance imaging, video‐otoscopy, myringotomy; cytological assessment of 30 and bacteriology of 28 effusions; histology and immunohistochemistry (CD3 for T‐lymphocytes, Pax5 for B lymphocytes and MAC387 for macrophages) of 10 middle ear sections. Results: Effusions were associated with neurological deficits in 6/16 (38%) and concurrent atopic dermatitis and otitis externa in 9/16 (56%) of live cases. Neutrophils and macrophages predominated on cytology (median 60 [range 2%‐95.5%] and 27 [2%‐96.5%]) whether culture of effusions was positive or not. In histology sections, the mucosa was thickened in affected dogs but submucosal gland dilatation occurred in affected and unaffected dogs. There was no bacterial growth from 22/28 (79%) of effusions. Bacteria isolated from the other 6 (21%) were predominantly Staphylococcus pseudintermedius (4/6, 67%). Conclusions and Clinical Importance: Clinical, morphological, and cytological findings in middle ear effusions of dogs and people suggest similar pathogeneses. Middle ear effusion of dogs could be a useful model of human otitis media with effusion. Such comparisons can improve understanding and management across species.